2022
DOI: 10.1111/hsc.13914
|View full text |Cite
|
Sign up to set email alerts
|

Applying a dyadic outcomes approach to supporting older carers and care‐recipients: A qualitative study of social care professionals in England

Abstract: There are an estimated 2 million older carers, aged 65 or over, in the UK. Older carers are more likely to care for a co-resident spouse/partner, provide high-intensity support and have their own health problems. The literature suggests that a 'dyadic outcomes approach' to social care (i.e. services and support that seek to understand and improve the quality of life of the older carer and the person they support, individually and together) may be especially beneficial for older carers. Such an approach may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The wider project consisted of a scoping literature review (Zhang et al, 2022), qualitative interviews with carers and care recipients (to be reported elsewhere) and interviews with social care professionals. The latter focused on professionals' views on the needs and outcomes of older carers, as well as their views on applying a dyadic QoL outcomes approach in practice, as reported elsewhere (Rand et al, 2022). They also captured data on professionals' views and experiences of their application of outcomes in practice, which are considered in the analysis presented here.…”
Section: Methods Study Designmentioning
confidence: 99%
“…The wider project consisted of a scoping literature review (Zhang et al, 2022), qualitative interviews with carers and care recipients (to be reported elsewhere) and interviews with social care professionals. The latter focused on professionals' views on the needs and outcomes of older carers, as well as their views on applying a dyadic QoL outcomes approach in practice, as reported elsewhere (Rand et al, 2022). They also captured data on professionals' views and experiences of their application of outcomes in practice, which are considered in the analysis presented here.…”
Section: Methods Study Designmentioning
confidence: 99%